EMOTION-RELATED PARENTING STYLES, SELF-CONTROL, AND EMPHATY ON ADOLESCENTS’ MORAL COMPETENCE - Khofifah, Ifa; Alfiasari; Nur Islamiah (Journal of Child, Family, and Consumer Studies, 2024)
The rapid pace of modern life poses a significant challenge for adolescents as they navigate the complexities of moral development and fulfill their developmental obligations. Several factors, including parental influences and adolescent characteristics, play a crucial role in shaping their moral development. This study examined the impact of family dynamics, adolescent characteristics, emotion-related parenting styles, self-control, and empathy on adolescent moral competence. Conducted in the Bandung City area, the study employed an explanatory research design and utilized a quantitative survey method with a sample of 110 pairs of high school students aged 15-18 and their parents. Results revealed that girls exhibited higher levels of empathy than boys and that self-control tended to decrease with grade level. Additionally, parents with a college education were more likely to employ emotion-coaching strategies. While there was no significant correlation between emotion-related parenting styles and adolescent moral competence, self-control and empathy demonstrated a positive and influential relationship with moral development in adolescents.